The Supervisory System of Conventional Online Lending in Aceh Following the Enforcement of Qanun Number 11 of 2018: A Study on Criminal Elements in Online Lending Transactions - Maulana, Muhammad; Ramly, Arroyyan; Yuhasnibar, Yuhasnibar; Alidar, EMK. (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Online Service lending has become a widely used financial product due to its accessibility, including in Aceh, which has implemented Qanun Number 11 of 2018 concerning Islamic Financial Institutions that prohibits interest-based lending practices. Therefore, this study focuses on the supervision of conventional online lending conducted by the government in Aceh following the implementation of Qanun Number 11 of 2018. This research adopts a descriptive method with data collected through interviews. The findings indicate that, to date, conventional online service lending (pinjol) operations in Aceh remain unrestricted, with no limitations imposed on their activities. In Aceh, stakeholders have yet to take concrete measures to curb or prohibit conventional online lending practices. Consequently, many consumers in Aceh, including educated individuals such as teachers and students, as well as the general public, have been trapped in debt and faced payment defaults. Therefore, strategic actions are required from both the Aceh government and religious scholars (ulama) to collaborate and synergize with relevant institutions such as the Financial Services Authority and Bank Indonesia to curb conventional fintech practices in Aceh, in accordance with the provisions outlined in Qanun Number 11 of 2018 on Sharia Financial Institutions in Aceh